2017
DOI: 10.1159/000481804
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Contrast Induced Nephropathy Through the Activation of SIRT1-PGC-1α-Foxo1 Signaling in Mice

Abstract: Background/Aims: SIRT1 activation promotes the resistance of renal tubular cells to oxidative stress, and resveratrol is known as a SIRT1 activator. Methods: Resveratrol was injected intraperitoneally with iohexol for 24 hours. NRK-52E cells were pretreated with resveratrol for 24 hours and then exposed to iohexol for 3 hours. Renal function was measured by serum creatinine and cell survival was assessed by MTT assay. We investigated whether resveratrol attenuates oxidative stress and apoptosis in contrast-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 45 publications
(47 reference statements)
1
45
0
Order By: Relevance
“…In NRK-52E rodent tubular cells, CM caused oxidative stress and decreased cell viability by downregulation of SIRT1 [21]. Transfection with SIRT1 siRNA resulted in increased apoptosis in these cells treated with CM [21]. These findings indicated that CM downregulated SIRT1, leading to increased cell apoptosis ( Table 1).…”
Section: Roles Of Silent Information Regulator 1 (Sirt1) In Cinmentioning
confidence: 91%
See 2 more Smart Citations
“…In NRK-52E rodent tubular cells, CM caused oxidative stress and decreased cell viability by downregulation of SIRT1 [21]. Transfection with SIRT1 siRNA resulted in increased apoptosis in these cells treated with CM [21]. These findings indicated that CM downregulated SIRT1, leading to increased cell apoptosis ( Table 1).…”
Section: Roles Of Silent Information Regulator 1 (Sirt1) In Cinmentioning
confidence: 91%
“…SIRT1 is a histone deacetylase of nicotinamide adenine dinucleotide (NAD + ), which mainly exists in the nucleus [20]. In NRK-52E rodent tubular cells, CM caused oxidative stress and decreased cell viability by downregulation of SIRT1 [21]. Transfection with SIRT1 siRNA resulted in increased apoptosis in these cells treated with CM [21].…”
Section: Roles Of Silent Information Regulator 1 (Sirt1) In Cinmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetic peripheral neuropathy, overexpression of Sirt1 can increase axonal growth through Sirt1/ PGC-1α/ TFAM axis and improve mitochondrial oxidative metabolism (40). It has also been shown that Sirt1/PGC-1α signaling pathway can further regulate the role of uncoupling protein 2(UCP2) or Forkhead box protein O1(FOXO1) in reducing oxidative stress and neuronal apoptosis (41,42). In our study, decreasing Sirt1 reduced the expression of PGC-1α and increased apoptosis, resulting in intracellular increased MDA and decreased SOD, which are related to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, FOXO1 siRNA transfection reduced the protein expression of p-mTOR in PA-treated HK-2 cells, which may explain the finding that no more MCP-1 was expressed in the PA+FOXO1 siRNA group compared with the PA group. Recently, certain reports have suggested a role for FOXO1 in renal protection (27,28). However, further investigation is required to explore whether FOXO1 is beneficial or detrimental in kidney diseases.…”
Section: Discussionmentioning
confidence: 99%